Patterns of avian diversification in Borneo: The case of the endemic Mountain Black-eye (Chlorocharis emiliae) - Gawin, Dency F.; Mustafa, Abdul Rahman; Mohamad Fizl, Sidq Ramji; Smith, Brian Tilston; Lim, Haw Chuan; Moyle, Robert G.; Sheldon, Frederick H. (The American Ornithologists' Union, 2014)
The Mountain Black-eye (Chlorocharis emiliae) is an endemic white-eye (Zosteropidae) of Borneo with a unique ‘‘sky island’’ distribution. We compared mitochondrial ND2, ND3, Cytb, and control region DNA sequences (2,194 nucleotides) to study the phylogeographic relationships of five populations of this species that span its range: Mounts Kinabalu, Trus Madi, Murud, Mulu, and Pueh. These comparisons showed that black-eyes are divided into two main clades that correspond generally to subspecific morphological groups: one in Sabah, Malaysia (Kinabalu and Trus Madi), and one in Sarawak, Malaysia (Murud, Mulu, and Pueh). The genetic and morphologic subdivision of black-eyes disputes the expected merging of populations during the Last Glacial Maximum (LGM), when montane forest presumably expanded and provided the opportunity for currently isolated populations to intermingle. Instead the genetic aging of black-eye populations indicates they diversified long before the LGM, and either did not expand sufficiently in range during the LGM to reach one another, or were reproductively isolated by the time of the LGM and thus prevented from interbreeding. Moreover, the subdivision between black-eyes in Sabah and Sarawak means that this species (and probably several other montane species) has a phylogeographic structure remarkably similar to Borneo’s lowland bird populations, which are presumed to have evolved under different paleo-geographic conditions. The similar phylogeographic pattern found in both montane and lowland species requires that we rethink the causes of bird population diversification on the island of Borneo.